2015
DOI: 10.1037/a0038660
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization and play therapy processes between two therapists and a child with Asperger’s disorder.

Abstract: The British Association of Play Therapists (BAPT) provides a definition of play therapy (PT) that emphasizes humanistic ideals such as using nondirective play techniques to enable the child's inner resources to bring about growth and change. These therapeutic change processes have never been submitted to empirical testing, partly because of the paucity of valid, reliable instruments to assess child psychotherapy process. Identifying empirically supported change processes is crucial to discovering which change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 35 publications
1
33
0
1
Order By: Relevance
“…The application of the CPQ to study the psychotherapy process with children at Long Island University under the direction of Geoff Goodman (Athey-Lloyd & Goodman, 2010;Fischel, 2012;Goodman, in press;Goodman & Athey-Lloyd, 2011;Goodman & Mavrides, 2010;Goodman, Reed, & Athey-Lloyd, 2015) and at the Anna Freud Centre under the direction of Nick Midgley (Ruzansky, 2007;Schneider, Midgley, & Duncan, 2010;Schneider, Pruetzel-Thomas, & Midgley, 2009) has yielded some interesting preliminary findings. Relevant to the present study, Schneider et al (2009) demonstrated that the CPQ items representing therapist technique significantly differentiated PDT process from CBT process, whereas the CPQ items representing the child's attitudes and behaviors reflected similar child presentations between the two treatment models.…”
Section: The Child Psychotherapy Process Q-setmentioning
confidence: 97%
“…The application of the CPQ to study the psychotherapy process with children at Long Island University under the direction of Geoff Goodman (Athey-Lloyd & Goodman, 2010;Fischel, 2012;Goodman, in press;Goodman & Athey-Lloyd, 2011;Goodman & Mavrides, 2010;Goodman, Reed, & Athey-Lloyd, 2015) and at the Anna Freud Centre under the direction of Nick Midgley (Ruzansky, 2007;Schneider, Midgley, & Duncan, 2010;Schneider, Pruetzel-Thomas, & Midgley, 2009) has yielded some interesting preliminary findings. Relevant to the present study, Schneider et al (2009) demonstrated that the CPQ items representing therapist technique significantly differentiated PDT process from CBT process, whereas the CPQ items representing the child's attitudes and behaviors reflected similar child presentations between the two treatment models.…”
Section: The Child Psychotherapy Process Q-setmentioning
confidence: 97%
“…() demonstrated the discriminant validity of CPQ when comparing sessions between two models of psychotherapy, PP and CBT. In addition, several studies have confirmed the interrater reliability obtained with the procedure (Goodman & Athey‐Lloyd, ; Goodman et al ., ; Ramires et al ., , ). In all of them, independent analyses of different sets of child psychotherapy sessions (ranging from 9 to 123 sessions) conducted by trained coders have reached agreement indices above 0.70 (intraclass correlation).…”
Section: Methodsmentioning
confidence: 96%
“…The interrater reliability, in all sessions, ranged from 0.62 to 0.81 (mean 0.73). These results are similar to previous studies (Goodman, ; Goodman et al ., ; Ramires et al ., , ). Subsequently, the means of the CPQ assessments were calculated to generate the composite score that was used in the subsequent analyses.…”
Section: Methodsmentioning
confidence: 96%
“…14 Similar to studies with adult patients, studies of child psychotherapy prototypes have indicated that psychotherapies do not always correspond to their theoretical assumptions and that one treatment may simultaneously exhibit characteristics of different approaches. 8,13,15 Likewise, there is evidence that characteristics of the dyad may influence the degree of similarity between the treatment and the prototypes. 13,15 However, despite development of the PDT, CBT, and RF prototypes by Goodman et al, 8 there are still gaps regarding prototypical psychotherapy processes with children.…”
Section: Child Psychotherapy Prototypesmentioning
confidence: 99%
“…8,13,15 Likewise, there is evidence that characteristics of the dyad may influence the degree of similarity between the treatment and the prototypes. 13,15 However, despite development of the PDT, CBT, and RF prototypes by Goodman et al, 8 there are still gaps regarding prototypical psychotherapy processes with children. A lack of prototypes focusing on specific regions may be an obstacle to analysis of the psychotherapeutic processes performed in different locations, considering that conceptions about such processes may vary between countries or continents.…”
Section: Child Psychotherapy Prototypesmentioning
confidence: 99%